Teenage prostitution and the future of the female adolescents in Nigeria (2002)
Nigeria has a large number of adolescents living and making a living on the streets. This has been attributed to economic factors and exposure to all forms of risks. The result is the proliferation of prostitution among the adolescents with its attendant problems. This article considers the different forms of adolescent prostitutes: those in brothels, street walkers, call girls, and casual, part-time, or floating prostitutes, as well as the trafficking of adolescent girls across international borders. The causes of adolescent prostitution in Nigeria are largely economic, sociological, and socioeconomic factors. A two-dimensional approach was adopted in considering the attitude to prostitution. Coping mechanisms include endurance, self-medication, seeking medical attention, and adaptation. The effects of prostitution are psychological reactions, psychosocial damage, and the political implication, which damages the image of the nation. Approaches to combat adolescent prostitution in Nigeria include legislative steps, governmental efforts, policy making, awareness programs, and the efforts of nongovernmental organizations, community conscientization, and societal measures.